Gender differences in factors associated with hypertension in Peru: Analysis of the National Demographic and Health Survey 2017 - Romero Giraldo, Milagros (2020)
Introduction. High blood pressure (HBP) is a leading cause of death worldwide, where the male sex is the most affected group. Objetives. Determine the gender differences of the factors associated with HBP in the Peruvian population over 18 years of age. Methods. A secondary analysis of the 2017 National Demographic and Health Survey was performed. Crude (RP) and adjusted (RPa) prevalence ratios and 95% confidence intervals (95% CI) were calculated using generalized linear models of the Poisson family between the dependent variable (HBP) and independent. Results. The prevalence of HBP was found to be 17,8% in men and 11,4% in women. Age, being overweight and obese increased the likelihood of HBP. While being from the rest of coast, mountain range and jungle decreased the likelihood of HBP in both sexes. Conclusions. There is a higher prevalence of HBP in the male sex and factors such as age, overweight and obesity increased the likelihood of HBP.